Antiphospholipid Antibody Positive Sera Enhance Endothelial Cell Procoagulant Activity – Studies in a Thrombosis Model - Oosting, Janine D; Derksen, Ronald H W M; Blokzijl, Laya; Sixma, Jan J; de Groot, Philip G (Thrombosis and Haemostasis, 1992)
The effect of sera and IgG from 12 patients with systemic lupus erythematosus (SLE) on the endothelial cell (EC) procoagulant activity (PCA) was investigated in an in vitro thrombosis model. Six of the 12 SLE sera contained antiphospholipid antibodies (aPL).EC were stimulated for 8 h at 37° C with or without 50 pM tumor necrosis factor (TNF) in culture medium containing 20% patient or control serum. Then the endothelial cell matrix (ECM) was isolated and subsequently exposed in a perfusion chamber to circulating normal whole blood, anticoagulated with low molecular weight heparin (LMWH). The PCA of the ECM was determined as the amount of generated fibrinopeptide A (FPA) in samples taken before and after perfusion. Furthermore, cross sections were made of the perfused matrix and analyzed for platelet adhesion and aggregate formation.All six aPL containing sera induced a small, but significant increase of ECM procoagulant activity. When added in combination with a low dose of TNF (50 pM), a synergistic enhancement of ECM procoagulant activity was found. The FPA generation was increased to 150–614% from the values obtained after stimulation with TNF and control serum. Also a shift towards the formation of larger platelet thrombi was observed. After stimulation with TNF and patient serum the surface of ECM covered with large aggregates (> 5 µm) was increased by 124–329% compared to the results obtained after stimulation with control serum and TNF. When patient sera were depleted from IgG the effects were strongly decreased.These data show that the potentiation of TNF-induced PCA formation by aPL containing sera from patients with SLE leads to enhanced thrombus formation in an in vitro thrombosis model. This may help explain the increased thrombotic tendency in these patients.